Fha Deficient Bordetella pertussis Isolates in Iran with 50 Years Whole Cell Pertussis Vaccination - Samaneh Saedi; Azadeh Safarchi; Faranak Tayebzadeh Moghadam; Siamak Heidarzadeh; Vajihe Sadat Nikbin; Fereshteh Shahcheraghi (Tehran University of Medical Sciences, 2021)
Background: Bordetella pertussis, a highly contagious respiratory. Notably, the resurgence of pertussis has recently been associated with the lacking production of vaccine virulence factors. This study aimed to screen pertactin (Prn) and filamentous hemagglutinin (Fha) production in Iran with 50 years' whole cell vaccine (WCV) immunization program. Methods: Overall, 130 B. pertussis isolates collected from Pertussis Reference Laboratory of Iran during 2005-2018. Real-time PCR was performed by targeting IS481, ptxP, IS1001 and IS1002 for species confirmation of B. pertussis. Western-blot was used to evaluate the expression of virulence factors (pertactin and filamentous hemagglutinin). Results: All tested B. pertussis isolates expressed Prn and all except two isolates expressed Fha. We have sequenced genomes of these strains and identified differences compared with genome reference B. pertussis Tohama I. Conclusion: Many countries reporting Prn and Fha-deficiency due to acellular vaccine (ACV) pressure. Our results demonstrate in a country with WCV history, Fha-deficient isolates may rise independently. However, Prn-deficient isolates are more under the ACV pressure in B. pertussis isolates. Continues surveillance will provide a better understanding of the effect of WCV on the evolution of the pathogen deficiency.